1994
DOI: 10.2307/3431762
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Repair Inhibition in Lead- and Cadmium-Induced Genotoxicity: A Review

Abstract: Compounds of lead and cadmium have been shown to be carcinogenic to humans and experimental animals. However, the underlying mechanisms are still not understood. In mammalian cells in culture, lead(lIl) is weakly mutagenic after long incubation times and generates DNA strand breaks only after treatment with high, toxic doses. Cadmium(ll) induces DNA strand breaks and chromosomal aberrations, but its mutagenic potential is rather weak. However, both metals exert pronounced indirect genotoxic effects. Lead(ll) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 31 publications
2
47
0
1
Order By: Relevance
“…In our assay, PbCl 2 was found to be genotoxic only in LS-174T cells, with a high and significant increase in H2AX phosphorylation. This genotoxic potential has also been reported in other studies, in which it was mainly explained by interference of lead with the DNA repair system [Hartwig, 1994;Restrepo et al, 2000]. None of the concentrations of lead we tested were found to be cytotoxic in either of the two cell lines tested.…”
Section: Discussionsupporting
confidence: 89%
“…In our assay, PbCl 2 was found to be genotoxic only in LS-174T cells, with a high and significant increase in H2AX phosphorylation. This genotoxic potential has also been reported in other studies, in which it was mainly explained by interference of lead with the DNA repair system [Hartwig, 1994;Restrepo et al, 2000]. None of the concentrations of lead we tested were found to be cytotoxic in either of the two cell lines tested.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, several authors have demonstrated a protective role of several antioxidants of natural sources against clastogeny induced by several agents in bone marrow cells of mice (Jagetia et al 2003;Liopiz et al 2004). Hartwig (1994) suggested that lead genotoxicity may occur by indirect DNA repair, and Albert & Robert (1991), suggested that specific DNA damage does not determine production (and frequency) of chromosomal aberrations, but rather that the substrate available during repair is the determining factor. So we suggest that the three extracts of O. majorana provide variable protection to genetic material indicated by reduction of the number of micronucleus, total aberrant cells or different types of chromosomal aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Pb can interact with zinc binding sites of human protamine and inhibits protamine binding to consensus sequences in DNA. One consequence of this interaction between Pb and protamine may cause decrease in protection of DNA to mutagens [Silbergeld et al, 2000, Hartwig, 1994].…”
Section: Introductionmentioning
confidence: 99%